Awareness of Seizure First Aid among the population in Jazan, Saudi Arabia: A survey Study - Faisal Hakami; Khalid M. Hakami; Shaden A. Zaalah; Afnan A. Alamer; Ghaidaa H. Alharbi; Mohammed Awaf; Sulaiman Hamdi; Anas E. Ahmed; Amal H. Mohamed; Abdulaziz Alhazmi; Tahir Hakami (Heliyon, 2023)
Background: First aid during a seizure is critical, but many people in Jazan, Saudi Arabia may not know what to do. This is because epilepsy is often stigmatized in the region and regarded as a spiritual or mental disorder. This study investigated the awareness of seizure first aid among the population living in Jazan. Methods: An online survey was conducted. Healthcare workers and people who had never heard of epilepsy were excluded. Participants were asked to identify correct measures of seizure first aid from a list of 20 statements [9 correct and 11 incorrect]. A composite awareness score was calculated by subtracting the number of incorrect statements from the number of correct statements. Participants were classified into three groups: high, intermediate, and low awareness. Logistic regression was used to identify factors associated with high awareness. Results: Of the 1215 participants, 80.5 % had low awareness of seizure first aid. The most common correct responses were clearing the area of dangerous objects (91.3 %), putting a pillow under the neck (69.3 %), and timing the seizure (68.5 %). However, only 32.2 % knew to tell the person what happened after the seizure. The most common misconception was that an ambulance should be called immediately, regardless of the details (88.3 %). Other common misconceptions included putting something in the person's mouth (87.5 %), holding them down (83.0 %), taking out their contact lenses (79.9 %), and giving antiseizure medications orally (73.2 %). People who previously watched an educational video on seizure first aid (OR = 4.27, 95 % CI = 1.48–12.34, p = .007) or who knew someone with epilepsy (OR = 9.01, 95 % CI = 2.82–28.83, p < .001) were more likely to have a high awareness of seizure first aid. Conclusion: The study found that most people in Jazan, Saudi Arabia do not know how to provide first aid for seizures. The findings inform future research and highlight the need for increased education and training on seizure first aid in this region.